Evaluation of Air Quality Status Near the Industrial Zone of Brega City Using Pollution Indicators - A.M. Alghamq, Mona; A.M. Falani , Tawfig (Scientific Journal of University of Benghazi, 2024)
Air pollution has grown to be a serious environmental problem in recent years, having an impact on both the environment and human health. Air quality indicators were calculated using the U.S. Environmental Protection Agency procedure in order to assess the state and quality of air surrounding Brega city. The study examined the air quality during the period of February 2020 to June 2021, using an average standard of 24 hours to measure pollutants such as sulfur dioxide, nitrogen oxides, respirable suspension particles, and suspended particles in four different locations. The findings showed that the levels of air pollution for sulfur dioxide, nitrogen oxides, PM10, and PM2.5 were consistently above the allowable limit at all sampling sites and that the relative air quality index fell within the severe air pollution range.